The impact of human capital and ICT index on local economic growth in Vietnam - Tam, Cao Minh; Phong, Nguyen Anh; Chinh, Le Van (Edelweiss Applied Science and Technology, 2024)
This study aims to examine the factors of human capital and technology (ICT) that impact the economic growth of localities in Vietnam in the period 2016-2021. The study also evaluates the interactive impact between information technology factors and human capital factors on economic growth. The data used is based on secondary data of 63 Vietnamese provinces and cities in the period 2016-2021, extracted directly from the General Statistics Office and Vietnamese business white papers. Data on indicators representing ICT are collected through the Vietnam ICT Readiness Index for Development and Application Report released by the Ministry of Information and Communication. Using SGMM will allow to overcome model defects such as multicollinearity, autocorrelation, heteroscedasticity and endogenous variables. The results show that the variables of the rate of labor over 15 years old, or the rate of workers with vocational training, have a positive impact on economic growth, while the factors of the number of people attending secondary school or spending on Education has a negative impact on local economic growth. The technology index (ICT) has a positive impact while the information technology human resource index has a negative impact on growth. Under the interactive impact of ICT, it can increase growth but can also reduce economic growth at a higher level. These results help provide some policy implications to help improve economic growth for localities in the next period by increasing the use of technology and continuously improving the quality of human capital.